SOCIAL AND PSYCHOLOGICAL ASPECTS OF DEVELOPMENT OF RELATIVE RESPONSIBILITY IN MODERN ENTREPRENEURS (CAHIERS MAGELLANES-NS, 2024)
This article is a logical continuation of the topic aimed at developing a concept for ensuring the economic development of the country, methodological foundations of psychological activity, as well as recommendations for identifying socio-psychological factors that develop responsibility of interpersonal relations among entrepreneurs and improving the formation of responsibility of relations.